2018
DOI: 10.1055/s-0038-1661360
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Cochlear Size of Cochlear Implant Candidates

Abstract: Introduction The cochlear anatomy varies in each individual, and that has an impact on decisions regarding the insertion of electrodes. The measurement of the cochlear size is the routine examination required to choose the proper cochlear implant (CI) electrodes. Objective To acquire normative data on the size of the cochlea (length, width, height, scala timpani [ST] height, cochlear duct length [CDL]) of CI candidates in Medan, Indonesia. Methods This descriptive study was conducted ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
2
19
0
2
Order By: Relevance
“…In this systematic review, the data were obtained from 56 studies 2–5,11,12,14–17,19,20,22–26,28–30,32–37,39–45,53–74 . However, there were 65 different subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review, the data were obtained from 56 studies 2–5,11,12,14–17,19,20,22–26,28–30,32–37,39–45,53–74 . However, there were 65 different subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…The variability of cochlear length 11,35–38 between individuals and the potential for personalized preoperative assessment to improve clinical outcomes has motivated several methods to estimate the CDL. Historically, histologic direct measurements were the first method to analyze the CDL and its variability 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Each step is completely automated to avoid introducing the error and variability that arise in many of the previously reported methods that rely on manual landmark identification. 11,[35][36][37] The automated system is also fast and efficient, scalable, and does not require specialized training to perform. These considerations represent a substantiative advantage of the system presented over existing automated methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zahara et al 13 and Grover et al 14 reported on the cochlear size variation by measuring both A value and B value within the Indian and Indonesian population, respectively. Alanazi and Alzhrani 15 reported on the cochlear size variation between Saudi and non-Saudi populations just by measuring the A value.…”
Section: Discussionmentioning
confidence: 99%